Leif Lewin, Samhället och de organiserade intressena, Stockholm: Norstedts, 1992, 135 s.; Bö Rothstein, Den korporativa staten., Stockholm: Nordstedts, 1992, 374 s. - Munk Christiansen, Peter (Politica, 1992)
-